The Role of Ambulatory Assessment in Psychological Science - Trull, Timothy J.; Ebner-Priemer, Ulrich (Current directions in psychological science : a journal of the American Psychological Society, 2014)
We describe the current use and future promise of an innovative methodology, ambulatory assessment, that can be used to investigate psychological, emotional, behavioral, and biological processes of individuals in their daily lives. The term "ambulatory assessment" encompasses a wide range of methods used to study people in their natural environment, including momentary self-report, observational, and physiological methods. We emphasize applications of ambulatory assessment that integrate two or more of these methods, discuss the smartphone as a hub or access point for ambulatory assessment, and discuss future applications of ambulatory-assessment methodology to the science of psychology. We pay particular attention to the development and application of wireless body area networks that can be implemented with smartphones and wireless physiological monitoring devices, and we close by discussing future applications of this approach to matters relevant to psychological science.